Project Management for the Built Environment Study Notes - Pheng, Low Sui (Management in the Built Environment,, 2018)
This book presents the fundamentals of project management as applied in the built environment and more specifically for the construction industry. It presents the project management body of knowledge (PMBOK) using practical examples to show how various project management principles and concepts can be applied in practice. Providing study notes for students and aspiring project management professionals in the construction industry, each of the 13 chapters includes a set of comprehensive revision questions that allow readers to reflect on what they have learned. The book offers an introduction to what project management is all about as well as the project life cycles, stakeholders and organizations involved. It explains the project management processes and how these processes are applied in integration, scope, time, cost, quality, human resource, communications, risk and procurement management. It concludes with ethics and professional conduct in the project management profession.